Enhanced Building Information Models Using IoT Services and Integration Patterns - Isikdag, Umit.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book explains how to combine and exploit sensor networks and internet-of-things (IoT) technologies and Web-service design patterns to enrich and integrate Building Information Models (BIMs). It provides approaches and software architectures for facilitating the interaction with (and between) BIMs through Web services, and for enabling and facilitating the fusion of the information residing in such models or of information acquired from IoT technologies. The proposed software architectures are presented in the form of design patterns. This information fusion will facilitate many novel application fields ranging from emergency response, to urban monitoring and surveillance, and to smart buildings. The book consists of 8 chapters. The first 2 chapters focus on the basics of BIMs, while chapter 3 presents fundamental service-oriented architecture patterns for complex information models. Subsequently, chapters 4 and 5 elaborate on the hardware and software side of IoT, with a special focus on their use for BIMs. Chapter 6 provides advanced SOA patterns for BIMs, while chapter 7 details patterns for IoT, and for BIM and IoT information fusion. Lastly, chapter 8 summarizes the work and provides an outlook on promising future developments. Overall, the book will be beneficial for researchers and developers in the fields of building information models, IoT applications, and systems integration.
CHAPTER 1 BUILDING INFORMATION MODELS: AN INTRODUCTION -- CHAPTER 2 THE FUTURE OF BUILDING INFORMATION MODELING: BIM TWO POINT ZERO -- CHAPTER 3 FOUNDATIONAL SOA PATTERNS FOR COMPLEX INFORMATION MODELS -- CHAPTER 4 INTERNET OF THINGS: SINGLE BOARD COMPUTERS -- CHAPTER 5 INTERNET OF THINGS: SOFTWARE PLATFORMS -- CHAPTER 6 ADVANCED SOA PATTERNS FOR BUILDING INFORMATION MODELS -- CHAPTER 7 SENSOR SERVICE ARCITECTURES FOR BIM ENVIRONMENTS -- CHAPTER 8 SUMMARY AND FUTURE OUTLOOK.
Keywords: Computer science; Special purpose computers; Software engineering; Application software; Building -- Superintendence; Construction industry -- Management; Construction superintendence; Electrical engineering; Computer Science; Computer Applications; Construction Management; Software Engineering; Special Purpose and Application-Based Systems; Communications Engineering, Networks; Electronic books